2021
DOI: 10.1177/23259671211024199
|View full text |Cite
|
Sign up to set email alerts
|

Return to Play and Player Performance After Achilles Tendon Rupture in UEFA Professional Soccer Players: A Matched-Cohort Analysis of Players From 1999 to 2018

Abstract: Background: Achilles tendon rupture (ATR) is a potentially career-ending injury in professional athletes. Limited information exists regarding return to play (RTP) in professional soccer players after this injury. Purpose: To determine the RTP rate and time in professional soccer players after ATR and to evaluate player performance relative to matched controls. Study Design: Cohort study; Level of evidence, 3. Methods: We evaluated 132 professional soccer players who suffered an ATR between 1999 and 2018. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
1
13
0
3
Order By: Relevance
“…This study also revealed that 11.8% of the included players did not maintain their previous levels, playing in lower categories after injury, and 11.8% of players who returned to played sustained an Achilles tendon re-rupture during their careers. The present series found that professional football players who suffered an ATR had a mean age at the time of injury of 28.7 years, whereas other studies found mean ages of 27.49 and 27.2 years (4,10). This may confirm how ATR could be considered an injury of the mature athlete (11).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…This study also revealed that 11.8% of the included players did not maintain their previous levels, playing in lower categories after injury, and 11.8% of players who returned to played sustained an Achilles tendon re-rupture during their careers. The present series found that professional football players who suffered an ATR had a mean age at the time of injury of 28.7 years, whereas other studies found mean ages of 27.49 and 27.2 years (4,10). This may confirm how ATR could be considered an injury of the mature athlete (11).…”
Section: Discussionsupporting
confidence: 68%
“…Sports that involve frequent acceleration and changes of direction with excessive eccentric loads on the Achilles tendon (AT) are considered to impose a high risk of ATR (3). The incidence of ATR in the general population ranges from 4.7 to 24 per 100,000 and has shown a consistent upward trend over a 15-year period and involvement of middle-aged people (4,5). AT ruptures can be divided into acute, when diagnosed or treated within 6 weeks, or chronic (6,7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rupture of the Achilles tendon is a common injury among athletes, and the incidence of ruptures has increased over the past four decades. 1 , 2 , 3 , 4 , 5 , 6 A recent population study in Sweden found that over an 11-year time period, the increase of Achilles ruptures in men and women increased by 17% and 22%, respectively. The reported overall incidence for males and females was 55.2 per 100,000 person-years and 14.7 per 100,000 person-years, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…발꿈치힘줄 파열(아킬레스건 파열, Achilles tendon rupture; ATR)은 반복적인 미세외상, 저혈관 성(hypovascular) 및 퇴행성 변화와 같은 외재적 요인과 신체의 컨디션이 좋지 않은 상황에서 고강도의 달리기나 점프 상황 등 내재적 요인이 결합되면서 발생할 수 있다 [6]. 엘리트 축구 선수는 경기 중에 다양한 뱡향으로 폭 발적인 변화를 수행하기 위해 발꿈치힘줄의 극심한 부 하에 자주 노출되면서 수술이 필요한 급성 ATR 위험이 높아진다 [7].…”
unclassified